DAYA TERIMA DAN KANDUNGAN ZAT GIZI MIKRO SERABI YANG DIPERKAYA TEPUNG TEMPE DAN TEPUNG IKAN TERI (Stolephorus sp - Lydia fanny (Media Gizi Pangan, 2019)
ABSTRACT Children under five begin to have difficulty eating or just like snacks that are classified as empty calories and nutrition in general.  Therefore it is necessary to enrich local snacks as an alternative for handling nutritional problems.  One of the local snacks that can help improve nutritional problems is serabi with the addition of tempe flour and anchovy flour.  This study aims to determine the iron content of serabi with the addition of tempe flour and anchovy flour.  This research is a type of laboratory research in the field of food.  The serabi formula with the addition of formula concentrations of tempe flour and anchovy flour are F1 (10%: 5%), F2 (15%: 5%), and F3 (25%: 5%).  The method of analysis of iron content is AAS (Atomic Absorption Spectrophotometer).  The data obtained were analyzed by computer programs using the Friedman test.  The results showed that the iron content was highest at a concentration of 10%: 5%.  The addition of tempe flour and anchovy flour did not have a significant effect on color, aroma, texture and taste.  From the most preferred aspect of serabi color on the addition of tempe flour and anchovy flour the concentration of 10%: 5% while the most preferred aspects of texture, aroma and taste on the addition of tempe flour and anchovy flour concentration of 10%: 5%, 15%:  5%, and 25%: 5%.  It can be concluded that the addition of tempe flour and anchovy flour gives increased levels of iron in the serabi.  The addition of tempe flour and anchovy flour do not have a significant effect on color, aroma, texture and taste in all three concentrations.Keywords: Serabi, tempe flour, anchovy flour